2022
DOI: 10.1155/2022/4722647
|View full text |Cite
|
Sign up to set email alerts
|

SIRT3-Mediated CypD-K166 Deacetylation Alleviates Neuropathic Pain by Improving Mitochondrial Dysfunction and Inhibiting Oxidative Stress

Abstract: Numerous studies have shown that mitochondrial dysfunction manifested by increased mitochondrial permeability transition pore (mPTP) opening and reactive oxygen species (ROS) level, and decreased mitochondrial membrane potential (MMP) plays an important role in the development of neuropathic pain. Sirtuin3 (SIRT3), a nicotinamide adenine dinucleotide (NAD+)-dependent histone deacetylase, has been shown to inhibit mitochondrial oxidative stress. However, the role of SIRT3 in neuropathic pain is unclear. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 59 publications
2
22
0
Order By: Relevance
“…Gain and loss of function was used to prove USP11 could ameliorate ferroptosis and mitigate IVDD by increasing Sirt3 in vitro. Previous studies have showed that Sirt3 relives neuropathic pain [ 82 , 83 ], thus the in vivo experiments were further performed in the current study. Notably, we confirmed that USP11 depletion promotes oxidative stress-induced ferroptosis by degrading Sirt3, leading to more severe IVDD and poor pain-related behavioral scores.…”
Section: Discussionmentioning
confidence: 99%
“…Gain and loss of function was used to prove USP11 could ameliorate ferroptosis and mitigate IVDD by increasing Sirt3 in vitro. Previous studies have showed that Sirt3 relives neuropathic pain [ 82 , 83 ], thus the in vivo experiments were further performed in the current study. Notably, we confirmed that USP11 depletion promotes oxidative stress-induced ferroptosis by degrading Sirt3, leading to more severe IVDD and poor pain-related behavioral scores.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to our findings, a study found that TIPE2 reduced the expression of TAK1, thereby inhibiting the activated pathway of NF- κ B and further improving sciatic nerve injury-induced neuropathic pain [ 19 ]. A growing number of studies suggest that the development and maintenance of neuropathic pain were related to mitochondrial dysfunction and abnormal oxidative stress [ 21 , 22 ]. In this study, the levels and activities of SOD, CAT, MDA, and GSH were tested, and the results showed that nab-paclitaxel treatment could downregulate antioxidant levels and upregulate oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Animal experiments have shown that abnormal opening of the MPTP after ischaemic stroke leads to mitochondrial calcium overload, changes in mitochondrial membrane potential, the release of cytochrome C, and disruption of the electron respiratory chain, which leads to rapid apoptosis and irreversible brain damage ( Yang Y. et al, 2021 ). Current research shows that three main molecules are involved in MPTP opening, CypD, VDAC1, and ANT1, which are all downstream molecules of SIRT3 ( Yan et al, 2022 ). In particular, OPA1, acetylated by SIRT3 at K926 and K931, regulates mitochondrial dynamics, mitochondrial respiration, and mitochondrial membrane fusion and renewal ( Samant et al, 2014 ; Chan, 2020 ).…”
Section: The Function Of Sirt3 In Brain Injurymentioning
confidence: 99%